Thermoresponsive release of viable microfiltrated Circulating Tumor Cells (CTCs) for precision medicine applications. Issue 22 (1st October 2015) - Ao, Zheng; Parasido, Erika; Rawal, Siddarth; Williams, Anthony; Schlegel, Richard; Liu, Stephen; Albanese, Chris; Cote, Richard J.; Agarwal, Ashutosh; Datar, Ram H.
Abstract : Stimulus responsive release of Circulating Tumor Cells (CTCs), with high recovery rates from their capture platform, is highly desirable for off-chip analyses. Abstract : Stimulus responsive release of Circulating Tumor Cells (CTCs), with high recovery rates from their capture platform, is highly desirable for off-chip analyses. Here, we present a temperature responsive polymer coating method to achieve both release as well as culture of viable CTCs captured from patient blood samples.